Hubungan Faktor Demografi Dan Stimulus Lingkungan Internal Toko Dengan Pembelian Impulsif - Suwantari, Ni Nyoman; Sri Ardani, I Gusti Agung Ketut (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
Normal 0 false false false EN-US X-NONE X-NONE The purpose of this study was to determine whether demographic factors had a significant association with impulsive purchases at supermarkets Tiara Dewata and also to determine whether a store environmental stimulation had a significant association with impulsive purchases at supermarkets Tiara Dewata. This research was conducted in the city of Denpasar , Bali precisely in Supermarket Tiara Dewata with sample was 170 respondents. The technique used is purposive sampling and data collection methods in this study , namely a questionnaire with a Guttman scale , while data analysis techniques using descriptive analysis and chi square test. The results showed that the demographic characteristics of gender just who has a significant relationship with impulsive purchases , while the stimulus variable stores the internal environment , only the layout of the store that has a significant relationship with impulse purchases. suggestions for the management of the supermaket Tiara Dewata should display the product at the entrance of the store and also should always check the lighting , audio instrument, and also fragrances in-store. Keywords : Demographic Factors, Store Environmental Stimulation , Impulsive Purchase /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}